From accidental project manager to intentional project leader: a reset whose time has come - Pinto, Jeffrey K.; Davis, Kate; Turner, Neil (Elsevier, 2025)
This essay revisits the enduring figure of the “accidental project manager” and questions its continued relevance in today’s increasingly complex and politicized project environments. While the concept remains a useful metaphor in some sectors, the profession must now reckon with deeper shifts in power, conflict, and contested notions of performance. Drawing on past work on power and politics in projects, as well as emerging evaluations of megaproject governance, the piece critiques the field’s overcorrection towards harmony and collaboration, arguing that conflict is not only inevitable but essential to effective project delivery. It further challenges prevailing assumptions about project performance, proposing that success is a negotiated and political construct rather than an objective outcome. The essay ultimately calls for a reimagining of the project professional — from accidental manager to political actor and leader — equipped to navigate the realities of today’s turbulent and multi-stakeholder environments.
Keywords: Building & Construction; 33 Built environment and design; 35 Commerce, management, tourism and services